Ethical Learning: The Workplace as a Moral Laboratory for Character Development. Issue 1 (16th November 2020) - Smith, Isaac H.; Kouchaki, Maryam
Abstract: In contrast to the view that businesses corrupt and bring out the worst in people, we propose that people's experiences at work can also lead to profound ethical learning and growth, and that organizations can be designed to help workers strive to become their best moral selves. To this end, we selectively review literature from the fields of organizational behavior, moral psychology, and behavioral ethics to identify five key barriers to ethical learning at work: defensiveness, overconfidence, selfishness, inexperience, and negative social influence. Then, to help leaders establish an organizational environment that helps workers overcome these barriers and promotes ethical learning and character development, we present five guiding principles (i.e., create an ethical culture, develop psychological safety, promote moral humility, foster prosocial motivation, and institutionalize moral reflection) and offer specific recommendations related to each.